Determination of Priority Elements of Vigilance in the Use of Pesticides based on Difficulty and Usefulness (A Supporting Study for Law and Policy in Health) - Ilyas Ibrahim1, I Ketut Sudiana2, H J Mukono3, Suhartono4, Heru Santoso Wahito Nugroho5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The use of pesticides is still a problem for public health, therefore we need a regulation by the authorities, which can lead to the behavior of using pesticides correctly. This is part of the area of law and health policy. Pesticide poisoning can cause breathing difficulties, headaches, neurological or psychological effects, and skin irritation and mucous membranes. The purpose of this study is to provide an overview of some elements of vigilance in the use of chemical pesticides for farmers. The variables studied were difficulty and usefulness with eight elements, namely the use of personal protective equipment (PPE), pesticide storage, pesticide use procedures, use of pesticide doses, duration and frequency of pesticide spraying, maintaining equipment cleanliness, pesticide spraying according to wind direction and time of pesticide spraying. The sample size of this study was 100 respondents from the community who knew about the use of pesticides throughout Indonesia. The research instrument used was a Google form questionnaire sent to respondents via Whatsapp social media. The data that has been collected is analyzed descriptively to get an idea of which elements are the priorities for improvement. Referring data analysis result, the elements with high difficulty and usefulness together were use of pesticide doses and procedures for using pesticides. Thus, the two elements selected as priority elements will be fixed first. It is suggested that the pesticide control policy makers can develop regulations by prioritizing the two main elements, without ignoring the other six elements. In addition, it is also recommended that other control efforts be made that can be recommended to related parties in the area of law and health policy, related to the prevention of health problems caused by the use of pesticides.